2019
DOI: 10.1371/journal.pone.0221190
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infection among household contacts of primary cases, a comparative cross-sectional study

Abstract: Background Intestinal parasitic infection affects 3.5 billion people in the world and mostly affecting the low socioeconomic groups. The objectives of this research works were to estimate the prevalence and determinants of intestinal parasitic infection among family members of known intestinal parasite infected patients. Methods and materials A comparative cross-sectional study design was implemented in the urban and rural settings of Mecha district. The data were collected from August 2017toMarch 2019 from in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
2
5
3
2
Order By: Relevance
“…Another important risk factor that contributed to the high prevalence of STHs infection among adolescents and adults in Bibugn Woreda was consumption of raw vegetables. The prevalence of STHs was higher in study participants who used raw vegetables than in participants who do not eat raw vegetables, but the difference was not statistically significant, which contradicts with previous study findings from Ethiopia [ 35 ]. In addition, STH prevalence was higher in males than in females, but the difference was not statistically significant, which contradicts with findings from coastal area of Kenya [ 21 ], Bench Maji Zone [ 22 ], and Bushulo village, Southern Ethiopia [ 34 ], where males were significantly at higher risk of STHs compared with females.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another important risk factor that contributed to the high prevalence of STHs infection among adolescents and adults in Bibugn Woreda was consumption of raw vegetables. The prevalence of STHs was higher in study participants who used raw vegetables than in participants who do not eat raw vegetables, but the difference was not statistically significant, which contradicts with previous study findings from Ethiopia [ 35 ]. In addition, STH prevalence was higher in males than in females, but the difference was not statistically significant, which contradicts with findings from coastal area of Kenya [ 21 ], Bench Maji Zone [ 22 ], and Bushulo village, Southern Ethiopia [ 34 ], where males were significantly at higher risk of STHs compared with females.…”
Section: Discussioncontrasting
confidence: 99%
“…Adults and adolescents who had no toilet in their compound were 3.68 times more likely to acquire STHs than those who had toilet in their compound. This finding agrees with findings from Ethiopia [ 35 ]. This is because it minimizes parasite transmission from open defecation which is suitable for parasite distribution.…”
Section: Discussionsupporting
confidence: 93%
“…A. lumbricoides were the most occurring intestinal parasite in the present study was in both boys and girls students, in boys student 58.09% (n=122) and girls student 57.01% (n=65) which was found to be higher than the study lead by Khan et al (2017c) Khan et al (2018); 7.76% reported from Swat, Feleke et al (2019) reported 8.5%prevalence of A. lumbricoides from Ethiopia. The second most prevalent intestinal parasite in the present study was hookworm in both boys and girls students, in boys 41.90% (n=88) and girls student 38.59% (n=44).…”
Section: Discussioncontrasting
confidence: 59%
“…The COVID-19 affects all ages (Liu et al 2020 ), and countries have issued policies to prevent this disease, such as social distancing and staying at home (WHO 2020 ). Since the prevalence of IPIs is directly associated with environmental sanitation, overcrowding, and personal hygiene (Feleke et al 2019 ), health education is effective in reducing IPIs. Therefore, due to the observance of personal and social health during the COVID-19 pandemic, the current study aimed to assess the prevalence of IPIs among patients referred to hospitals affiliated to Shiraz University of Medical Sciences by reviewing the available data of hospital information system databases in the pre- and post-COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%